Planning a Large-scale Assessment of Student Achievement : What are Essential Elements of the Assessment Framework? - Luna Bazaldua, Diego Armando (Washington, DC: World Bank, 2022)
An important part of planning a large-scale assessment of student achievement is developing the framework for the assessment. In many education projects financed by the World Bank and other international organizations, the development of an assessment framework is included as one of the results indicators for the project. This note addresses frequently asked questions about the contents of an assessment framework. Examples of assessment frameworks are included at the end. An assessment framework describes what is being assessed, why it is being assessed, how it is being assessed, and who is being assessed. A well thought-through assessment framework supports the development of appropriate assessment instruments, sample designs, implementation strategies, analytical approaches, and reporting structures. Indeed, assessment frameworks are one of the building blocks for strengthening national assessment systems. At the same time, frameworks are only guiding documents and should be flexible enough to allow for necessary changes to the design, conduct, or analysis of the assessment in response to conditions on the ground. This guidance note discusses how to develop an assessment framework for a large-scale assessment exercise that will provide information on overall learning levels in an education system. Typically, such assessments are national in scope, but they may also be sub-national or international.